Proceedings of the 5th ASEAN Conference on Psychology, Counselling, and Humanities (ACPCH 2019) 2020
DOI: 10.2991/assehr.k.200120.049
|View full text |Cite
|
Sign up to set email alerts
|

The Significant Role of Culture to Value Differences: Socio-Emotional Challenge in Digital Era

Abstract: People in each region have different values in the social and emotional aspects of life. Culture has an important role in value differences. Children's attitudes and behaviors during his growth and development also differ in accordance with the culture in which they are growing. This particular culture can be seen in Javanese (andhap asor), Bugis-Makassarese (siri), and Papuan (more tendencies in emotional expressive). The purpose of this study is to seek the differences between Javanese, Bugis-Makassarese, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…Schoeps et al [ 48 ] observe in a recent study with Spanish adolescents that girls perceive and understand emotions better than boys, although they present greater emotional problems. In contrast to our data, in works such as that of Rahayu and Mustikasari [ 55 ], with Asian children aged 10 to 13 years, no inequalities were observed according to this variable. López-González and Oriol [ 49 ] also found no differences in emotional competence between boys and girls in the first cycle of ESO; however, they did find differences in the second cycle, but in favour of boys.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Schoeps et al [ 48 ] observe in a recent study with Spanish adolescents that girls perceive and understand emotions better than boys, although they present greater emotional problems. In contrast to our data, in works such as that of Rahayu and Mustikasari [ 55 ], with Asian children aged 10 to 13 years, no inequalities were observed according to this variable. López-González and Oriol [ 49 ] also found no differences in emotional competence between boys and girls in the first cycle of ESO; however, they did find differences in the second cycle, but in favour of boys.…”
Section: Discussioncontrasting
confidence: 99%
“…By contrast, girls tend to achieve higher values in variables related to interpersonal relationships [50,54]. Nevertheless, other studies confirmed that gender did not always have influence on socio-emotional skills [49,55].…”
Section: Introductionmentioning
confidence: 99%
“…Self-reporting socio-emotional skills: The Social Emotional Competence Questionnaire (SECQ) by Zhou and Ee [39] was used, following the guidelines of Casel [21,22] which was already validated in other populations in Eastern countries and Asia [32,38], Spain [40], and other European countries [41]. The instrument includes five described domains organized into 25 items on a Lickert type scale from 1 to 6, where 1 means totally disagree with the proposed statement and 6 means totally agree with the proposed statement.…”
Section: Instrumentsmentioning
confidence: 99%
“…In addition, we considered how gender could constitute an intervening variable, as boys tend to achieve higher scores in self-management [32][33][34] and girls in interpersonal skills [35,36]. However, there are also studies that concluded that there are no differences with respect to gender in socio-emotional skills [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, some are too long for children and youth populations, while others are aimed at adult populations and groups with specific characteristics, which makes it difficult for participants to self-report [16]. Faced with this problem, Zhou and Ee [17] designed the Social Emotional Competence Questionnaire (SECQ), a questionnaire that assesses socio-emotional competence in the adolescent period, which has already proved to be reliable and has been validated in other populations in Eastern and Asian countries [18,19]. The authors argued that it would be necessary to replicate their findings using students from other cultures, such as Western cultures, which are diverse and heterogeneous.…”
Section: Introductionmentioning
confidence: 99%